Improving Students’ Learning Outcomes in Problem Solving Through Problem Solving Method: Systematic Literature Review - Salwa Aiyesi Aiyesi; Sri Bona Ayu; Heru Kuswanto; Pretty Oktianti Menur Kusuma Putri (Jurnal Inovasi Pendidikan IPA, 2026)
Problem-solving must be owned by students in learning process, which is the ability of students to solve physics problems effectively. Ineffective problem solving skills will impact on students’ learning outcomes. Then, structured and appropriate efforts are needed to improve students’ ability to solve physics problems. The particular study employed the Systematic Literature Review (SLR) method, which is designed to systematically identify, categorize, review, evaluate, and interpret relevant journal articles based on criteria. The SLR approach followed a structured and replicable process that ensures transparency and rigor in synthesizing existing research following the research objectives. The findings indicated that the difficulties experienced by students in learning physics are caused by several factors, such as: students’ thoughts that always consider physics as a difficult subject, the use of inappropriate learning methods, and limited facilities and infrastructure to support learning. In addition, there are internal factors, such as students difficulties in adapting to learning and the differences in students’ learning styles